Hard carbon negative electrode material and preparation method and application thereof
By introducing a hierarchical porous structure and a short-range ordered pseudographite structure into the hard carbon anode material, the problems of low efficiency and instability of existing hard carbon anode materials in sodium ion batteries are solved, and the Coulomb efficiency, capacity and cycling performance of the material are significantly improved.
Patent Information
- Application Number
- CN202510386848.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-31
AI Technical Summary
The existing hard carbon anode materials have low first-time Coulomb efficiency, platform capacity, magnification and cycle stability problems in sodium ion batteries, and the pore filling reaction in low-potential platform areas are generally low reversibility, which has caused serious safety problems such as sodium dendrites growth and electrolyte decomposition.
By selecting suitable sodium and/or lithium salts for dehydration and condensation reaction with phenolic resin and/or lignin and carbonize, a nano-scale hard carbon anode material with a graded porous structure and a short-range ordered pseudographite structure is prepared. The pore size distribution of this material is 1.85-30 nm micropores and mesopores, and the average closed pore diameter is 1.75-2.0 nm, with more C=O functional groups and large average layer spacing.
The first-time Coulomb efficiency, platform capacity, rate performance and cycle stability of hard carbon materials have been significantly improved. As the negative electrode material of sodium ion battery, the charging specific capacity of the first round is higher than 421mAh g-1 at 0.1C current density, and the efficiency of the first round is ≥93%; as the negative electrode material of lithium ion battery, the charging specific capacity of the first round is higher than 500mAh g-1 at 0.1C current density, and the efficiency of the first round is ≥80%.
Smart Images

Figure CN119905585A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary battery negative electrode materials, and in particular to a hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, excellent cycle performance, and long service life. They are widely used in portable electronic products, electric vehicles, and large-scale energy storage. Similarly, sodium resources are abundant, evenly distributed around the world, and inexpensive. Sodium-ion batteries are seen as a highly promising complementary technology, especially for large-scale energy storage systems. Therefore, the development of lithium-ion and sodium-ion batteries is of great significance. However, the application of sodium-ion batteries faces multiple challenges, including low first coulombic efficiency, specific capacity, rate performance, and poor cycle stability. The limited availability of suitable electrode materials, especially the construction of high-quality negative electrodes, poses a major challenge to the development of sodium-ion batteries. Carbon negative electrode materials have played a significant role in improving battery energy storage performance, improving safety, and reducing costs, and have triggered a wave of research and development in academic and industrial institutions around the world. Hard carbon is composed of pores, defects, and graphite crystallites, with a complex structure. It has abundant resources, high theoretical specific capacity, and low specific capacity relative to Na. + / Na has great commercial potential due to its advantages such as low working voltage. The typical cross-current charge-discharge curve of sodium storage in hard carbon anode can be divided into a high potential slope region (>0.1 V) and a low potential platform region (<0.1 V). In the high potential slope region (>0.1 V), because there are too many defects and unfavorable functional groups on the hard carbon surface, sodium ions in the electrolyte are captured, resulting in irreversible sodium loss and low first coulombic efficiency in the hard carbon slope region. Although the storage mechanism of sodium is still unclear, extensive studies have shown that the platform capacity is mainly related to the deposition of sodium in closed pores. However, although the sodium ion embedding and pore filling of hard carbon at low potential (<0.1 V) contribute to the main capacity, the pore filling reaction in the low potential platform region is generally low in reversibility, which triggers serious safety issues such as sodium dendrite growth and electrolyte decomposition. At the same time, the slow ion diffusion kinetics limits its rate performance, resulting in unsatisfactory energy and power density of the assembled sodium ion battery. Therefore, it is urgent to develop simple, effective and controllable methods to simultaneously regulate the nano-closed pores, surface defects and pseudo-graphite structure of hard carbon to comprehensively improve the first coulombic efficiency, platform capacity, rate and cycle stability of hard carbon.
[0003] Among the negative electrode materials of lithium-ion batteries, the current commercial lithium-ion battery negative electrode is mainly graphite-based materials. According to the lithium storage mechanism of LiC6 between graphite layers, its theoretical specific capacity is only 372 mAh g -1, the room for improvement is very limited, and the diffusion of lithium between graphite layers also restricts the rate performance. As the demand for battery energy and power performance in downstream applications continues to increase, there is an urgent need to develop new carbon materials with high specific capacity and rate performance. Hard carbon has more active sites and larger interlayer spacing relative to graphite. Therefore, as a new generation of lithium-ion battery negative electrode material, hard carbon has a very broad development prospect. In recent years, significant progress has been made in the application of hard carbon negative electrode materials in lithium-ion battery negative electrodes, but most hard carbons still face challenges or bottlenecks such as low lithium storage capacity and the need to improve rate performance. Summary of the invention
[0004] The object of the present invention is to provide a high initial efficiency, high capacity hard carbon negative electrode material with excellent rate performance and cycle stability, which can avoid or improve the relevant defects mentioned in the above-mentioned prior art part.
[0005] According to a first aspect of the present invention, there is provided a hard carbon negative electrode material, wherein the hard carbon negative electrode material has a spherical shape; The particle size of the hard carbon negative electrode material is 100 to 300 nm; the specific surface area of the hard carbon negative electrode material is 80 to 100 m 2 / g; The hard carbon negative electrode material has a hierarchical porous structure, and the pore size of the hierarchical porous structure is micropores and mesopores with a range of 1.85 to 30 nm; The average closed pore diameter of the hard carbon negative electrode material is 1.75 to 2.0 nm; The hard carbon negative electrode material has a short-range pseudo-graphite structure, an average lateral size of 3.38-3.50 nm, and an average longitudinal size of 0.82-0.84 nm.
[0006] A hard carbon negative electrode material according to the present invention has at least the following beneficial effects: (1) The hard carbon negative electrode material of the present invention has more C=O functional groups and a large average interlayer spacing of 0.39 nm-0.4 nm, which is beneficial to improving the sodium storage capacity in the slope region.
[0007] (2) The hard carbon negative electrode material of the present invention has a hierarchical porous structure and a short-range ordered pseudo-graphite structure, and sodium ions and lithium ions can be quickly transported and diffused, which is beneficial to improving the rate performance of the hard carbon material.
[0008] (3) The hard carbon negative electrode material of the present invention, as a negative electrode material for sodium ion batteries, has a first cycle charge capacity of more than 421 mAh g at a current density of 0.1C. -1 , the first coulombic efficiency is ≥93%; as a negative electrode material for lithium-ion batteries, the first cycle charge capacity is higher than 500mAh g at a current density of 0.1C -1 , the first coulombic efficiency is ≥80%.
[0009] (4) The hard carbon negative electrode material of the present invention, as a negative electrode material for sodium ion batteries, still has a current density of 320 mAh g -1 As the negative electrode material of lithium-ion batteries, it still has a specific capacity of 400mAhg at a current density of 10C. -1 Specific capacity.
[0010] (5) The hard carbon negative electrode material of the present invention, as a negative electrode material for sodium ion batteries, still has a capacity retention rate of 80% after 600 cycles at 0.5C.
[0011] According to a second aspect of the present invention, there is provided a method for preparing the hard carbon negative electrode material, comprising the following steps: S1, dissolving phenolic resin and / or lignin and alkali metal salt in ethanol and water respectively to obtain two mixed solutions, mixing the two mixed solutions, and stirring them thoroughly to obtain a uniform mixed solution; S2, pouring the uniform mixed solution obtained in step S1 into a closed reactor, heating and performing a dehydration condensation reaction to obtain a solid gel material; S3, drying the solid gel material obtained in step S2 to obtain a dry solid material; S4. Carbonizing the dried solid material obtained in step S3 at high temperature under a protective atmosphere to obtain a hard carbon negative electrode material.
[0012] The method for preparing a hard carbon negative electrode material according to the present invention has at least the following beneficial effects: (1) The present invention selects appropriate sodium salt and / or lithium salt to react with phenolic resin and / or lignin for dehydration condensation and carbonization to form nano-scale hard carbon powder. The obtained nano-scale hard carbon powder exhibits excellent first effect and reversible capacity, rate performance and cycle stability. The strategy of the present invention is more environmentally friendly, simple and convenient.
[0013] (2) The present invention selects a suitable sodium salt and / or lithium salt to react with phenolic resin and / or lignin to obtain a precursor through dehydration condensation reaction, which will produce more pores and an appropriate amount of sodium vapor or lithium vapor during the pyrolysis process, and these pores and sodium or lithium vapor directly affect the sodium insertion capacity, first coulomb efficiency, rate and cycle performance of the hard carbon negative electrode material. The present invention optimizes the internal pore structure and surface oxygen-containing functional groups and defect structures of the material by adjusting the type, content, preheating, carbonization and cooling of the phenolic resin material and the sodium salt and / or lithium salt.
[0014] (3) The present invention selects appropriate sodium salt and / or lithium salt to form pores and modify the structure of the hard carbon phase. The synthesized hard carbon does not require complex processes such as acid washing, which reduces the cost of preparing hard carbon, simplifies the process, and protects the environment.
[0015] (4) The present invention not only reduces equipment costs, plant costs, labor costs, etc. by reasonably controlling the carbonization heating rate, but also has low energy consumption and short time, greatly improving production efficiency.
[0016] In some embodiments of the present invention, the phenolic resin in step S1 is an alcohol-soluble and / or water-soluble phenolic resin.
[0017] In some embodiments of the present invention, the lignin in step S1 is alcohol-soluble and / or water-soluble lignin.
[0018] In some embodiments of the present invention, the alkali metal salt in step S1 is selected from sodium salt and / or lithium salt, the sodium salt is one or more of sodium carbonate, sodium sulfate, sodium acetate, sodium formate, sodium citrate, and sodium oxalate, and the lithium salt is lithium acetate and / or lithium carbonate.
[0019] In some embodiments of the present invention, the mass ratio of the phenolic resin to the alkali metal salt in step S1 is 1:0.02-1.
[0020] In some embodiments of the present invention, the heating temperature in step S2 is 160-200° C., and the dehydration condensation reaction time is 3-12 hours.
[0021] In some embodiments of the present invention, the carbonization temperature in step S3 is 1200° C. to 1600° C., the carbonization time is 1 to 10 h, and the carbonization heating rate is 2 to 10° C. / min.
[0022] In some embodiments of the present invention, the protective atmosphere in step S4 is an inert gas, and the flow rate of the protective atmosphere is 150-400 sccm.
[0023] The present invention utilizes a liquid phase method to evenly blend a sodium salt and / or lithium salt solution with a phenolic resin solution and / or a lignin solution, thereby ensuring the uniformity of the mixing of the two. In a high temperature and high pressure environment, the phenolic resin and / or the lignin undergo dehydration condensation, and during this process, the sodium salt and / or the lithium salt are evenly embedded in the condensed phenolic resin particles and / or the lignin particles and occupy a fixed space.
[0024] After mixing the phenolic resin and / or lignin solution with the alkali metal salt solution, the solid particle precipitate is obtained after the reaction is completed in the reactor. During the carbonization process of the solid particle powder obtained after drying, the sodium salt and / or lithium salt will decompose at the low temperature section of 400-600°C to generate new sodium salt and lithium salt and act as a template, and at the same time, the carbon etching gas is generated to initially form pores in the carbon matrix. After 600°C, the new sodium salt and lithium salt begin to react with the carbon to etch more microporous structures. As the temperature further increases and the time is extended, the micropores are gradually etched into mesopores and macropores, forming a hierarchical porous structure, and sodium and lithium elements are reduced at the same time. Sodium element and lithium element will become gaseous at high temperatures. During the further carbonization process at high temperature, new sodium salts and lithium salts will decompose to generate sodium oxide and lithium oxide. Sodium oxide and lithium oxide will continue to decompose to generate sodium vapor, lithium vapor and oxygen, creating space for the formation of pores and inhibiting the growth of pseudo-graphite domains. Sodium vapor and lithium vapor react with surface defects of hard carbon and oxygen-containing functional groups under high temperature to make up for the surface defects of hard carbon. At high temperatures greater than 1300°C, open pores gradually close to form closed pores. At the same time, sodium oxide and lithium oxide will completely decompose into gas at higher temperatures without leaving impurities, which will not affect the sodium storage performance of hard carbon. High-temperature trace sodium and lithium components migrate to the surface of hard carbon, inducing the formation of a thin and dense SEI film during the charge and discharge process to improve cycle stability.
[0025] According to a third aspect of the present invention, there is provided a use of the hard carbon negative electrode material in a secondary battery.
[0026] In some embodiments of the present invention, the secondary battery includes one of a sodium ion battery and a lithium ion battery.
[0027] In some embodiments of the present invention, the above-mentioned hard carbon negative electrode material is provided as the active material of the electrode, and is stirred and mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, and is scraped onto an aluminum foil current collector, and dried in a vacuum drying oven at 80°C for 24 hours to obtain an electrode sheet, which is cut into discs of a certain size, and a sodium sheet is used as a counter electrode. The electrolyte is selected from the sodium salts of NaBF4, NaPF6, NaClO4, NaFSI, and NaTFSI, and an organic solvent selected from dimethyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether to assemble a button battery.
[0028] In some embodiments of the present invention, the above-mentioned hard carbon negative electrode material is provided as the active material of the electrode, and is stirred and mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, and is scraped onto a copper foil current collector, and dried in a vacuum drying oven at 80°C for 24 hours to obtain an electrode sheet, which is cut into discs of a certain size, and a lithium sheet is used as a counter electrode. The electrolyte is selected from lithium salts of LiBF4, LiPF6, LiFSI, and LiTFSI, and an organic solvent selected from dimethyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether to assemble a button battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The first cycle charge and discharge curves of the nano-scale hard carbon prepared according to Example 1 and the hard carbon comparison sample prepared according to Comparative Example 1 are shown.
[0030] Figure 2 The figure is a rate performance diagram of the nano-scale hard carbon prepared according to Example 1 and the hard carbon comparison sample prepared according to Comparative Example 1.
[0031] Figure 3 The graph is a cycle performance diagram of the nano-scale hard carbon prepared according to Example 1 and the hard carbon comparison sample prepared according to Comparative Example 1.
[0032] Figure 4 This is a transmission electron microscope image of the nanoscale hard carbon prepared according to Example 1.
[0033] Figure 5 This is a high-resolution image of the nanoscale hard carbon prepared according to Example 1.
[0034] Figure 6 The X-ray diffraction patterns of the nano-scale hard carbon precursor prepared according to Example 1 and the hard carbon comparative sample precursor prepared according to Comparative Example 1 are shown.
[0035] Figure 7 The pore size distribution curve of the nano-scale hard carbon prepared according to Example 1 is shown in FIG. DETAILED DESCRIPTION
[0036] The present invention is described in detail below with reference to the accompanying drawings and specific examples.
[0037] Example 1 This embodiment provides a method for preparing a sodium acetate modified phenolic resin nano-scale hard carbon negative electrode material. The specific steps are as follows: Figure 4 As shown in the figure, the high-resolution image of the hard carbon negative electrode material is Figure 5 The pore size distribution curve of hard carbon negative electrode material is shown in Figure 7 shown.
[0038] (1) Dissolve 0.4 g of sodium acetate in 15 mL of deionized water to obtain a colorless transparent solution, then dissolve 4 g of thermosetting phenolic resin in 100 mL of anhydrous ethanol to obtain a light yellow phenolic resin solution. The obtained sodium acetate aqueous solution is mixed into the phenolic resin ethanol solution to obtain a wine red mixed solution.
[0039] (2) The obtained wine red mixed solution was poured into a polytetrafluoroethylene liner, and the mixture was heated in a hydrothermal oven at 180 degrees Celsius for 8 hours to polymerize to obtain a gel-like yellow polymer precipitate, which was then dried in an oven at 80 degrees Celsius for 24 hours to obtain a yellow powder.
[0040] (3) The obtained yellow powder was further carbonized in an argon atmosphere at a heating rate of 2 degrees Celsius per minute, a holding temperature of 1300 degrees Celsius, and a holding time of 2 hours to obtain a nano-scale spherical hard carbon material.
[0041] (4) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 421mAh g -1 The first coulombic efficiency is 93%, and the reversible capacity at 10C is 320 mAh g -1 , after 600 cycles, the capacity retention rate is greater than 80%.
[0042] (5) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 520mAh g -1 The first coulombic efficiency is 85%, and the reversible capacity at 10C is 423 mAh g -1 .
[0043] Example 2 This embodiment provides a method for preparing a sodium carbonate-modified phenolic resin nano-scale hard carbon negative electrode material, and the specific steps are as follows.
[0044] (1) The 0.4 g of sodium acetate in Example 1 was replaced with 0.5 g of sodium carbonate, and the other operation steps were kept consistent with Example 1 to obtain nano-scale spherical hard carbon.
[0045] (2) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 408mAh g -1 The first coulombic efficiency is 92% and the reversible capacity at 10C is 300mAh g -1 .
[0046] (3) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 505mAh g -1 The first coulombic efficiency is 83% and the reversible capacity at 10C is 420 mAh g -1 .
[0047] Example 3 This embodiment provides a method for preparing a sodium formate-modified phenolic resin nano-scale hard carbon negative electrode material, and the specific steps are as follows.
[0048] (1) The 0.4 g of sodium acetate in Example 1 was replaced with 0.6 g of sodium formate, and the other operation steps remained the same as in Example 1 to obtain nano-scale spherical hard carbon.
[0049] (2) The nano-scale spherical hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 400mAh g -1 The first coulombic efficiency is 90%, and the reversible capacity at 10C is 290 mAh g -1 .
[0050] (3) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 503mAh g -1The first coulombic efficiency is 81% and the reversible capacity at 10C is 400 mAh g -1 .
[0051] Example 4 This embodiment provides a method for preparing a sodium citrate-modified phenolic resin nano-scale hard carbon negative electrode material, and the specific steps are as follows.
[0052] (1) The 0.4 g of sodium acetate in Example 1 was replaced with 0.5 g of sodium citrate, and the other operation steps were kept consistent with Example 1 to obtain nano-scale spherical hard carbon.
[0053] (4) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 405mAh g -1 The first coulombic efficiency is 91%, and the reversible capacity at 10C is 304 mAh g -1 .
[0054] (5) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 510mAh g -1 The first coulombic efficiency is 82% and the reversible capacity at 10C is 410 mAh g -1 .
[0055] Example 5 This embodiment provides a method for preparing a sodium oxalate-modified phenolic resin nano-scale hard carbon negative electrode material, and the specific steps are as follows.
[0056] (1) The 0.4 g sodium acetate in Example 1 was replaced with 0.4 g sodium oxalate, and the other operation steps were kept consistent with Example 1 to obtain nano-scale spherical hard carbon.
[0057] (2) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 406mAh g -1The first coulombic efficiency is 89% and the reversible capacity at 10C is 298 mAh g -1 .
[0058] (3) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 513mAh g -1 The first coulombic efficiency is 80%, and the reversible capacity at 10C is 404 mAh g -1 .
[0059] Example 6 This embodiment provides a method for preparing a nano-scale hard carbon material of phenolic resin modified by sodium acetate and sodium formate, and the specific steps are as follows.
[0060] (1) The 0.4 g sodium acetate in Example 1 was replaced with 0.2 g sodium acetate plus 0.2 g sodium formate, the carbonization temperature was increased to 1600° C., and the other operation steps were kept consistent with Example 1 to obtain nano-scale spherical hard carbon.
[0061] (2) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 400mAh g -1 The first coulombic efficiency is 91%, and the reversible capacity at 10C is 302 mAh g -1 .
[0062] (3) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 510mAh g -1 The first coulombic efficiency is 81%, and the reversible capacity at 10C is 402 mAh g -1 .
[0063] Example 7 This embodiment provides a method for preparing a nano-scale hard carbon material of phenolic resin modified by lithium acetate and lithium carbonate, and the specific steps are as follows.
[0064] (1) The 0.4 g sodium acetate in Example 1 was replaced with 0.3 g lithium acetate plus 0.2 g lithium carbonate, and the carbonization temperature was increased to 1600° C. The other operation steps were the same as those in Example 1 to obtain nano-scale spherical hard carbon.
[0065] (2) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 406mAh g -1 The first coulombic efficiency is 90%, and the reversible capacity at 10C is 305 mAh g -1 .
[0066] (3) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 509mAh g -1 The first coulombic efficiency is 82% and the reversible capacity at 10C is 403 mAh g -1 .
[0067] Example 8 This embodiment provides a method for preparing a nano-scale hard carbon material of phenolic resin modified by sodium acetate and sodium formate, and the specific steps are as follows.
[0068] (1) The 0.4 g of sodium acetate in Example 1 was replaced with 0.2 g of sodium acetate and 0.2 g of sodium formate. The other steps remained the same as those in Example 1 to obtain nano-scale spherical hard carbon.
[0069] (2) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto an aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 411mAh g -1 The first coulombic efficiency is 92% and the reversible capacity at 10C is 310 mAh g -1 .
[0070] (3) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 515mAh g -1 The first coulombic efficiency is 80%, and the reversible capacity at 10C is 415 mAh g -1 .
[0071] Example 9 This embodiment provides a method for preparing a sodium acetate-modified lignin nano-scale hard carbon material, and the specific steps are as follows.
[0072] (1) The 4 g phenolic resin in Example 1 was replaced with 4 g lignin, and the other operation steps were kept consistent with Example 1 to obtain nano-scale spherical hard carbon.
[0073] (2) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 400mAh g -1 The first coulombic efficiency is 90%, and the reversible capacity at 10C is 301 mAh g -1 .
[0074] (3) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 510mAh g -1 The first coulombic efficiency is 83%, and the reversible capacity at 10C is 406 mAh g -1 .
[0075] Example 10 This embodiment provides a method for preparing a sodium carbonate and lithium acetate modified lignin nano-scale hard carbon material, and the specific steps are as follows.
[0076] (1) The 4 g phenolic resin in Example 1 was replaced by 4 g lignin, and the 0.4 g sodium acetate was replaced by 0.2 g sodium carbonate plus 0.3 g lithium acetate. The other operation steps were the same as those in Example 1 to obtain nano-scale spherical hard carbon.
[0077] (2) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 405mAh g -1 The first coulombic efficiency is 91%, and the reversible capacity at 10C is 302 mAh g -1 .
[0078] (3) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 511mAh g -1 The first coulombic efficiency is 80%, and the reversible capacity at 10C is 407 mAh g -1 .
[0079] Embodiment 11 This embodiment provides a method for preparing a sodium acetate-modified phenolic resin and / or lignin nano-scale hard carbon material, and the specific steps are as follows.
[0080] (1) The 4 g phenolic resin in Example 1 was replaced with 2 g phenolic resin plus 2 g lignin. The other operation steps remained the same as those in Example 1 to obtain nano-scale spherical hard carbon.
[0081] (2) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 418 mAh g -1 The first coulombic efficiency is 92%, and the reversible capacity at 10C is 323 mAh g -1 .
[0082] (3) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 517mAh g -1 The first coulombic efficiency is 81%, and the reversible capacity at 10C is 413 mAh g -1 .
[0083] Comparative Example 1 This comparative example provides a method for preparing a phenolic resin hard carbon negative electrode material, and the specific steps are as follows.
[0084] (1) Dissolve 4 g of thermosetting phenolic resin in 100 mL of anhydrous ethanol to obtain a light yellow phenolic resin solution. Then, mix 15 mL of deionized water into the phenolic resin ethanol solution to obtain a light yellow mixed solution.
[0085] (2) Pour the obtained light yellow mixed solution into a polytetrafluoroethylene liner, heat it in a hydrothermal oven at 180 degrees Celsius for 8 hours to polymerize to obtain a dark yellow polymer precipitate, and dry it in an oven at 80 degrees Celsius for 24 hours to obtain a dark yellow powder.
[0086] (3) The obtained dark yellow powder was further carbonized in an argon atmosphere at a heating rate of 2 °C per minute, a holding temperature of 1300 °C, and a holding time of 2 h to obtain a hard carbon material.
[0087] (4) The hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 303mAh g -1 The first coulombic efficiency is 80%, and the reversible capacity at 10C is 200 mAh g -1 .
[0088] (5) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 400mAh g -1 The first coulombic efficiency is 80%, and the reversible capacity at 10C is 340 mAh g-1 .
[0089] Comparative Example 2 This comparative example provides a method for preparing a lignin hard carbon negative electrode material, and the specific steps are as follows.
[0090] (1) Dissolve 4 g of lignin in 100 mL of anhydrous ethanol to obtain a lignin solution. Then, add 15 mL of deionized water into the lignin ethanol solution to obtain a uniform solution.
[0091] (2) The obtained solution was poured into a polytetrafluoroethylene liner, and heated in a hydrothermal oven at 180 degrees Celsius for 8 hours to polymerize to obtain a brown polymer precipitate, which was then dried in an oven at 80 degrees Celsius for 24 hours to obtain a brown powder.
[0092] (3) The obtained brown powder was further carbonized in an argon atmosphere at a heating rate of 2 °C per minute, a holding temperature of 1300 °C, and a holding time of 2 h to obtain a hard carbon material.
[0093] (4) The hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the aluminum foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a sodium sheet as the counter electrode and 1M NaPF6 ether as the electrolyte. The first cycle charging capacity was 340mAh g -1 The first coulombic efficiency is 84%, and the reversible capacity at 10C is 234 mAh g -1 .
[0094] (5) The nano-scale hard carbon material obtained above was used as the active material of the electrode, and was mixed with conductive carbon black and PVDF binder in a ratio of 88:8:4 to form a slurry, which was then scraped onto the copper foil current collector and dried in a vacuum oven at 80°C for 24 hours to obtain an electrode sheet, which was cut into discs of a certain size, and a button cell was assembled using a lithium sheet as the counter electrode and 1M LiPF6 ether as the electrolyte. The first cycle charging capacity was 403mAh g -1 The first coulombic efficiency is 73%, and the reversible capacity at 10C is 353 mAh g -1 .
[0095] Test Example 1 In this test example, button-type batteries were used to test the charge and discharge performance of Examples 1 to 11 and Comparative Examples 1 to 2 at room temperature (25° C.). The test results are shown in Table 1.
[0096] Table 1 Electrochemical performance of Examples 1 to 11 and Comparative Examples 1 to 2
[0097] Test Example 2 This test example tests the pore size distribution of Examples 1 to 11 and Comparative Examples 1 to 2. The test results are shown in Table 2.
[0098] Table 2 Pore volume distribution of Examples 1 to 11 and Comparative Examples 1 to 2
[0099] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A hard carbon negative electrode material, characterized in that: The hard carbon negative electrode material has a spherical shape; The particle size of the hard carbon negative electrode material is 100 to 300 nm; the specific surface area of the hard carbon negative electrode material is 80 to 100 m 2 / g; The hard carbon negative electrode material has a hierarchical porous structure, and the pore size of the hierarchical porous structure is micropores and mesopores with a range of 1.85 to 30 nm; The average closed pore diameter of the hard carbon negative electrode material is 1.75 to 2.0 nm; The hard carbon negative electrode material has a short-range pseudo-graphite structure, an average lateral size of 3.38-3.50 nm, and an average longitudinal size of 0.82-0.84 nm.
2. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The following steps are involved: S1, dissolving phenolic resin and / or lignin and alkali metal salt in ethanol and water respectively to obtain two mixed solutions, mixing the two mixed solutions, and stirring them thoroughly to obtain a uniform mixed solution; S2, pouring the uniform mixed solution obtained in step S1 into a closed reactor, heating and performing a dehydration condensation reaction to obtain a solid gel material; S3, drying the solid gel material obtained in step S2 to obtain a dry solid material; S4. Carbonizing the dried solid material obtained in step S3 at high temperature under a protective atmosphere to obtain a hard carbon negative electrode material.
3. The method for preparing a hard carbon negative electrode material according to claim 2, characterized in that: In step S1, the phenolic resin is an alcohol-soluble phenolic resin and / or a water-soluble phenolic resin, and the lignin is an alcohol-soluble lignin and / or a water-soluble lignin.
4. The method for preparing a hard carbon negative electrode material according to claim 2, characterized in that: The alkali metal salt in step S1 is selected from sodium salt and / or lithium salt.
5. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: In step S1, the sodium salt is one or more of sodium acetate, sodium carbonate, sodium sulfate, sodium formate, sodium citrate, and sodium oxalate, and the lithium salt is lithium acetate and / or lithium carbonate.
6. The method for preparing a hard carbon negative electrode material according to claim 2, characterized in that: In step S1, the mass ratio of the phenolic resin and / or lignin to the alkali metal salt is 1:0.02-1.
7. The method for preparing a hard carbon negative electrode material according to claim 2, characterized in that: The heating temperature in step S2 is 160-200° C., and the dehydration condensation reaction time is 3-12 hours.
8. The method for preparing a hard carbon negative electrode material according to claim 2, characterized in that: In step S3, the carbonization temperature is 1200° C. to 1600° C., the carbonization time is 1 to 10 hours, and the carbonization heating rate is 2 to 10° C. / min.
9. The method for preparing a hard carbon negative electrode material according to claim 2, characterized in that: The protective atmosphere in step S4 is an inert gas, and the protective atmosphere flow rate is 150-400 sccm.
10. Use of the hard carbon negative electrode material as claimed in claim 1 in a secondary battery.
Citation Information
Patent Citations
Negative-electrode active material for sodium-ion secondary battery, method for manufacturing said negative-electrode active material, and sodium-ion secondary battery
CN105247713A
Hard carbon material with lamellar structure
CN118825241A
Hard carbon with molecular sieve type closed cell structure as anode
CN119604994A
Composite resin-based hard carbon negative electrode material for sodium ion battery and preparation method of composite resin-based hard carbon negative electrode material
CN119725493A
Ceramic material and circuit substrate and its production
JP1999116333A
Cited By
Hard carbon negative electrode material and preparation method and application thereof
CN121565863A